Donor IL-18 rs5744247 polymorphism as a new biomarker of tacrolimus elimination in Chinese liver transplant patients during the early post-transplantation period: results from two cohort studies. (March 2015) - Fan, Junwei; Zhang, Xiaoqing; Ren, Lei; Chen, Dawei; Wu, Shaohan; Guo, Feng; Qin, Shengying; Wang, Zhaowen; Lin, Zhong; Xing, Tonghai; Sun, Xing; Peng, Zhihai
Aim: This study evaluated the relationships between IL-18 polymorphisms and tacrolimus elimination in Chinese liver transplant patients.Patients & methods : Eighty-four liver transplant patients from Shanghai (training set) and 50 patients from Shandong (validating set) were inculded. IL-18 polymorphisms (rs5744247, rs7106524, rs549908, rs187238 and rs1946518) and CYP3A5 rs776746 were genotyped.Results: In training set, daily drug dose, total bilirubin, donor CYP3A5 rs776746 and IL-18 rs5744247 genotypes were screened to construct prediction model for tacrolimus elimination. This model was confirmed in validating set (p < 0.001). Donor IL-18 rs5744247 polymorphism was an independent predictor of tacrolimus elimination in the first week after transplantation in both training (p = 0.008) and validating cohorts (p = 0.033).Conclusion: Donor IL-18 rs5744247 polymorphism may influence on tacrolimus elimination. Original submitted 16 July 2014; Revision submitted 12 November 2014